In Service Diagnosing of a Marine Diesel Engine Using Mean Indicated Pressure - Wontka, L. (Scientific Journal of Gdynia Maritime University, 2018)
The article presents possibilities of assessment of technical condition of a marine diesel engine using the mean indicated idle pressure. The paper was based on wide research material collected during engine diagnostics operated on naval ships from 1997 to 2018. The author was a member of diagnostic team conducting researches. The article shows problems related to this assessment and presents research methodology.